2010
DOI: 10.1124/jpet.110.172288
|View full text |Cite
|
Sign up to set email alerts
|

Selective Binding of Bladder Muscarinic Receptors in Relation to the Pharmacokinetics of a Novel Antimuscarinic Agent, Imidafenacin, to Treat Overactive Bladder

Abstract: The binding of orally administered imidafenacin, used to treat overactive bladders, to muscarinic receptors in rat tissue was characterized based on pharmacokinetics. The binding in six tissues including bladder tissue was measured using [N-methyl-3 H] scopolamine methyl chloride ([ 3 H]NMS). Pharmacokinetic parameters were estimated from measurements of the concentration of imidafenacin in serum, the bladder, and the submaxillary gland by liquid chromatography-mass spectrometry/mass spectrometry. The recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
56
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 23 publications
(34 reference statements)
4
56
1
Order By: Relevance
“…Since imidafenacin exhibited greater selectivity for the M 3 than M 2 subtype in CHO-K1 cells expressing human muscarinic receptors (4), the high affinity of [ 3 H]imidafenacin for muscarinic receptors in the human parotid gland reflects M 3 -subtype selectivity. In vivo functional and ex vivo muscarinic receptor binding experiments in rats (5,6) and clinical studies in humans (9,10) showed that imidafenacin selected the bladder over the exocrine gland. These in vivo results appear to contradict the M 3 -subtype selectivity observed in vitro, but in vivo bladder selectivity has been mainly attributed to the pharmacokinetic property of this agent (6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since imidafenacin exhibited greater selectivity for the M 3 than M 2 subtype in CHO-K1 cells expressing human muscarinic receptors (4), the high affinity of [ 3 H]imidafenacin for muscarinic receptors in the human parotid gland reflects M 3 -subtype selectivity. In vivo functional and ex vivo muscarinic receptor binding experiments in rats (5,6) and clinical studies in humans (9,10) showed that imidafenacin selected the bladder over the exocrine gland. These in vivo results appear to contradict the M 3 -subtype selectivity observed in vitro, but in vivo bladder selectivity has been mainly attributed to the pharmacokinetic property of this agent (6).…”
Section: Discussionmentioning
confidence: 99%
“…Yamada et al (6) and Seki et al (12) examined the competitive inhibitory effect of imidafenacin on [Nmethyl- 3 H]scopolamine methyl chloride (NMS) binding and revealed that it was a potent inhibitor of muscarinic receptor binding sites in rat and human bladders. Thus, investigating the direct binding properties of imidafenacin to bladder muscarinic receptors is of importance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Imidafenacin is the most bladder-selective anticholinergic available: it antagonizes both the M3 and M1 receptor subtypes in vitro and in vivo [Kobayashi et al 2007a[Kobayashi et al , 2007bYamada et al 2011b]. Furthermore, preclinical research indicates that the duration of receptor binding of imidafenacin is longer in the bladder than in the salivary glands, heart, colon and brain [Kobayashi et al 2007a[Kobayashi et al , 2007bYamada et al 2011b].…”
Section: Bladdermentioning
confidence: 99%
“…Furthermore, preclinical research indicates that the duration of receptor binding of imidafenacin is longer in the bladder than in the salivary glands, heart, colon and brain [Kobayashi et al 2007a[Kobayashi et al , 2007bYamada et al 2011b]. …”
Section: Bladdermentioning
confidence: 99%